2019
DOI: 10.3758/s13414-019-01865-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of content and intensity of thought on behavioral and pupil changes during active mind-wandering, off-focus, and on-task states

Abstract: Mind wandering (MW) is a pervasive phenomenon that occurs very frequently, regardless of the task. A content-based definition of MW holds that it occurs when the content of thought switches from an ongoing task and/or an external stimulus-driven event to self-generated or inner thoughts. A recent account suggests that the transition between these different states of attention occurs via an off-focus state. Following this suggestion, previous work relating MW to pupil size might have lumped attentional states t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…We believe that the answer will strongly depend on two main related factors, namely (i) the operational definition of MW and its characteristics (ii) the characteristics of the main task. In this sense, we agree with Konishi et al [52; see also 51,64], suggesting that the content of MW and the context in which it emerges are determinant for its relation to other neurocognitive variables (including pupil size).…”
Section: Discussionsupporting
confidence: 93%
“…We believe that the answer will strongly depend on two main related factors, namely (i) the operational definition of MW and its characteristics (ii) the characteristics of the main task. In this sense, we agree with Konishi et al [52; see also 51,64], suggesting that the content of MW and the context in which it emerges are determinant for its relation to other neurocognitive variables (including pupil size).…”
Section: Discussionsupporting
confidence: 93%
“…We believe that the answers to these questions will always depend on the exact characteristics of the main task and of the MW episodes. In this sense, we agree with Konishi et al (32; see also 31,45), suggesting that the content of MW and the context in which it emerges are determinant for its relation to other neurocognitive variables (including pupil size). Therefore, it is impossible, a priori, to predict the direction of pupil modulations for a new experimental setting.…”
Section: Discussionsupporting
confidence: 93%
“…With alpha = .05 and a hypothesized correlation of .3 among within-subject factors, simulation results show that a sample size of 40 can achieve over 80% power for both the interaction between attention and distractor presence as well as the post-hoc tests. The planned sample size is also comparable to previous studies examining the relationship between pupil size, task performance, and MW (e.g., Franklin, 2013;Jubera-García et al, 2019;Konishi et al, 2017;Smallwood et al, 2011;Unsworth & Robison, 2016.…”
Section: Participantssupporting
confidence: 67%
“…Previous studies examining the relationship between task-evoked pupillary response (phasic pupil size) found that MW was consistently associated with smaller task-evoked responses (e.g., Jubera-García et al, 2019;Mittner et al, 2014;Unsworth & Robison, 2016). An important difference between our task and theirs is that our task involves making overt and fast eye movements away from the screen center, which may occlude any effects on pupil dilation.…”
Section: Discussionmentioning
confidence: 97%